Exploring genetic diversity and population structure of a large grapevine (Vitis vinifera L.) germplasm collection in Türkiye - Kaya, Hilal Betul; Dilli, Yıldız; Oncu-Oner, Tulay; Ünal, Akay (Frontiers in Plant Science, 2023)
Grapevine (Vitis Vinifera L.) has been one of the significant perennial crops in widespread temperate climate regions since its domestication around 6000 years ago. Grapevine and its products, particularly wine, table grapes, and raisins, have significant economic importance not only in grapevine-growing countries but also worldwide. Grapevine cultivation in Türkiye dates back to ancient times, and Anatolia is considered one of the main grapevine migration routes around the Mediterranean basin. Turkish germplasm collection, conserved at the Turkish Viticulture Research Institutes, includes cultivars and wild relatives mainly collected in Türkiye, breeding lines, rootstock varieties, and mutants, but also cultivars of international origin. Genotyping with high-throughput markers enables the investigation of genetic diversity, population structure, and linkage disequilibrium, which are crucial for applying genomic-assisted breeding. Here, we present the results of a high-throughput genotyping-by-sequencing (GBS) study of 341 genotypes from grapevine germplasm collection at Manisa Viticulture Research Institute. A total of 272,962 high-quality single nucleotide polymorphisms (SNP) markers on the nineteen chromosomes were identified using genotyping-by-sequencing (GBS) technology. The high‐density coverage of SNPs resulted in an average of 14,366 markers per chromosome, an average polymorphism information content (PIC) value of 0.23 and an expected heterozygosity (He) value of 0.28 indicating the genetic diversity within 341 genotypes. LD decayed very fast when r2 was between 0.45 and 0.2 and became flat when r2 was 0.05. The average LD decay for the entire genome was 30 kb when r2 = 0.2. The PCA and structure analysis did not distinguish the grapevine genotypes based on different origins, highlighting the occurrence of gene flow and a high amount of admixture. Analysis of molecular variance (AMOVA) results indicated a high level of genetic differentiation within populations, while variation among populations was extremely low. This study provides comprehensive information on the genetic diversity and population structure of Turkish grapevine genotypes.